High precision in-cylinder gas thermometry using Laser Induced Gratings: Quantitative measurement of evaporative cooling with gasoline/alcohol blends in a GDI optical engine - Williams, B; Edwards, M; Stone, R; Williams, J; Ewart, P (2014)
The first application of Laser Induced Thermal Gratings Spectroscopy (LITGS) for precision thermometry in a firing GDI optical engine is reported. Crank-angle resolved temperature values were derived from LITGS signals generated in fuel vapour with a pressure dependent precision in the range 0.1-1.0% allowing differences in evaporative or charge cooling effects arising from a variety of ethanol and methanol blends with a model gasoline fuel to be quantified. In addition, fluctuations in temperature arising from cyclic variations in compression were directly detected and measured. © 2013 The Combustion Institute.